Letter from Dr. Carl D. Duncan to Patricia Whiting, February 10, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Dr. Carl D. Duncan discusses events of the day as well as future plans to fly to Portland.